2022
DOI: 10.1002/aepp.13283
|View full text |Cite
|
Sign up to set email alerts
|

European consumers' valuation for hybrid meat: Does information matter?

Abstract: This study investigates for the first time how the use of different information messages (i.e., health, sensory, and convenience benefits) about hybrid meat shapes British, Spanish, and Danish consumers' willingness to pay (WTP) for such products. Hybrid meats are products whereby a proportion of the meat has been replaced by plant-based proteins. Using a choice experiment (CE) involving hybrid burgers that vary across four attributes (i.e., ingredient, fat content, Carbon Trust label, and price), our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In particular, in the informed group, the patty received a slightly higher hedonic score than in the blind group, which emphasizes the role of knowing the nature of the product (i.e., made with 70% beef and 30% mushrooms). Furthermore, to promote the consumption of hybrid meat products, previous authors (Asioli et al., 2023; Banovic & Barone, 2021) have underlined the need to better understand the role of providing information, for instance by stressing the sensory or health benefits of the vegetable ingredients used.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in the informed group, the patty received a slightly higher hedonic score than in the blind group, which emphasizes the role of knowing the nature of the product (i.e., made with 70% beef and 30% mushrooms). Furthermore, to promote the consumption of hybrid meat products, previous authors (Asioli et al., 2023; Banovic & Barone, 2021) have underlined the need to better understand the role of providing information, for instance by stressing the sensory or health benefits of the vegetable ingredients used.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a diversity of hybrid meat products have been introduced on the market; these products are specifically designed to blend meat and plant-based ingredients in convenient ready to cook forms, such as burgers, sausages or minced products ( 3 ). Despite the novelty of this hybrid concept, some consumer studies have already been carried out ( 4 6 ), and recent research has focussed on understanding consumer attitudes toward such products, including consumers’ views on their formulation and different types of messaging on them ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a third objective of this study is to investigate how the search behaviors for presence or absence of certain characteristics across food products relate to underlying food choice motives. While reviews have identified healthiness as a key motivation for clean eating (Asioli et al , 2022; Chen et al , 2022), we investigate the heterogeneity in motives between the latent subgroups of individuals.…”
Section: Introductionmentioning
confidence: 99%